2019
DOI: 10.1186/s12885-019-5909-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T cell subsets are associated with clinical outcome of anti-VEGF-based 1st-line treatment of metastatic colorectal cancer patients: a prospective study with focus on primary tumor sidedness

Abstract: Background In a prospective study with long-term follow-up, we analyzed circulating T cell subsets in patients with metastatic colorectal cancer (mCRC) in the context of primary tumor sidedness, KRAS status, and clinical outcome. Our primary goal was to investigate whether baseline levels of circulating T cell subsets serve as a potential biomarker of clinical outcome of mCRC patients treated with an anti-VEGF-based regimen. Methods The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A combination of FOLFOXIRI with immunotherapy may revolutionize standard clinical care [70][71][72]. The presence of immune cells in the tumor microenvironment of mCRC after first-line chemotherapy treatment can be used to predict potential combinations with immunotherapy [72][73][74]. FOLFOX or FOLFOXIRI treatment triggers immune cell infiltration [74], increases the expression of immune-modulatory receptors and can prime and enhance for some time the immune cell activity at the tumor site [72,74].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of FOLFOXIRI with immunotherapy may revolutionize standard clinical care [70][71][72]. The presence of immune cells in the tumor microenvironment of mCRC after first-line chemotherapy treatment can be used to predict potential combinations with immunotherapy [72][73][74]. FOLFOX or FOLFOXIRI treatment triggers immune cell infiltration [74], increases the expression of immune-modulatory receptors and can prime and enhance for some time the immune cell activity at the tumor site [72,74].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a significant proportion of tumor-infiltrating CD4 + cells are Tregs ( Kim and Cantor, 2014 ). A high ratio of Tregs to cytotoxic CD8 + T cells is correlated with poor prognosis of patients with multiple cancer types, including pancreatic cancer, ovarian cancer, and colorectal cancer ( Preston et al, 2013 ; Tang et al, 2014 ; Bencsikova et al, 2019 ). Hence, the key to the treatment of solid tumors is to suppress the recruitment of Tregs to the TME or to inhibit their immunosuppressive functions.…”
Section: Swimming Together: Fish Players In Adaptive Immunitymentioning
confidence: 99%
“…It is worth noting, however, that most of these studies provide evidence of correlation but not causation between Treg levels and VEGF signaling. Most recently, a study by Bencsikova et al (62) demonstrated that the initial level of circulating lymphocytes in patients with metastatic colorectal cancer predicted the clinical outcomes of first-line treatment with bevacizumab, a mAb against VEGF. Interestingly, they also reported that low levels of circulating Tregs were…”
Section: Role Of Tregs In Promoting Angiogenesismentioning
confidence: 99%